5G Systems with Low Density Parity Check based Chanel Coding for Enhanced Mobile Broadband Scheme - Chen, Joy Iong Zong (IRO Journal on Sustainable Wireless Systems, 2020)
The 5G mobile communication standard based radio access technology (RAT) is analysed for implementation of several candidate coding schemes in this paper. The third generation partnership project (3GPP) in the 5G scenario based on the Enhanced mobile broadband (eMBB) scheme is considered. Factors like flexibility, complexity of computation, bit error rate (BER), and block error rate (BLER) are considered for the purpose of evaluation of the coding schemes. In order to evaluate the performance various applications and services, a suitable set is of parameters are provided. The candidate schemes considered for this purpose are polar codes, low density parity check (LDPC) and turbo codes. Fair comparison is performed by investigation of block lengths and obtaining suitable rates by proper design. In an additive white Gaussian noise (AWGN) channel, the performance of BLER / BER is obtained for diverse block lengths and code rates based on simulation. The simulation results show that the performance of LDPC is relatively efficient for various code rates and block lengths despite the better performance of polar codes at short block lengths. As an added advantage, LDPC codes also offer relatively low complexity.
Keywords: 3GPP; polar codes; LDPC; 5G; eMBB